Increasing Children's Basic Literacy Through Storybook Media - Triyanita, Triyanita; Mulyono, Rahmat (Universitas Wiralodra, 2023)
Activities to improve basic literacy through reading storybooks are carried out daily, one of the efforts to enhance students' Basic Literacy skills. This research aims to understand how storybooks are used as a medium to improve the basic literacy skills of early childhood. The subjects in this research were teachers, students, and parents of group B students at the Mertelu Guyangan PKK Kindergarten. Reading storybook media improves basic literacy by observing and gathering information regarding storybook reading activities by children, teachers, and parents at school, the types of books children like, and the benefits of reading storybooks in improving basic literacy skills based on observation and analysis.